2009
DOI: 10.1016/j.jtcvs.2008.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in esophageal cancer: Effect of neoadjuvant chemoradiotherapy followed by surgical intervention

Abstract: Neoadjuvant therapy has a significant effect on health-related quality of life, but this is transient, with recovery to baseline within 5 to 7 weeks after completion of induction therapy. Health-related quality of life decreases again after surgical intervention but returns to baseline levels within 3 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
3
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 23 publications
0
43
3
1
Order By: Relevance
“…4 Surgery can offer a 30% chance of cure in early-stage EC 5 and a 5-year overall survival rate of approximately 20% to 40%. 6,7 However, surgery for EC is associated with a high risk of severe complications in approximately 40% of patients, carries a risk of in-hospital death of up to 10%, and has a detrimental impact on quality of life (QoL). 8,9 Clearly, self-reported QoL information is important because it adds predictive value to the best available preoperative and postoperative prognosticators 10 and because it supplements informed decision making before surgery.…”
mentioning
confidence: 99%
“…4 Surgery can offer a 30% chance of cure in early-stage EC 5 and a 5-year overall survival rate of approximately 20% to 40%. 6,7 However, surgery for EC is associated with a high risk of severe complications in approximately 40% of patients, carries a risk of in-hospital death of up to 10%, and has a detrimental impact on quality of life (QoL). 8,9 Clearly, self-reported QoL information is important because it adds predictive value to the best available preoperative and postoperative prognosticators 10 and because it supplements informed decision making before surgery.…”
mentioning
confidence: 99%
“…However, it returns back to baseline within 3 months. At one year, HRQOL continues to improve when compared to preoperative baseline (9). It is important to note that although global/overall HRQOL appears to return to baseline/pre-treatment levels, the physical functioning component of HRQOL still remains poorer or worse than baseline/pre-treatment levels (9).…”
Section: Return To Baseline Hrqol After Therapymentioning
confidence: 91%
“…It was found that higher baseline FACT-E or ECS were both independently associated with better survival. Thus, pre-treatment HRQOL measures appeared to provide prognostication even when one controls for stage and treatments given (9,16,34). ECS, with its focused and shorter number of questions, consistently showed a larger effect size and tighter confidence intervals than FACT-E.…”
Section: Pre-treatment Hrqol As a Prognostic Toolmentioning
confidence: 92%
See 2 more Smart Citations